France
XI, 245 p.
Keywords: Against the broad historical background of economic globalisation and dwindling nation-state resources, this book examines the impact of the end of the Cold War and of the geo-political transformation of Europe on a wide range of issues, from changing perceptions of France's future world role to the internal ramifications of a new ideological and strategic environment. Multi disciplinary in focus, it draws on the expertise of historians, political scientists, sociologists and economists working in the field of French studies.